Democracy and efficiency in the economic enterprise - Pagano, Ugo, 1951-; Rowthorn, Bob (Routledge studies in business organization and networks, 2002)
The collapse of central planning was hailed as evidence of the economic and moral superiority of capitalism over any possible alternative. The essays in this book challenge that claim. The case for more democratic forms of enterprise management is considered from a variety of viewpoints. One chapter deals with the philosophical justification for enterprise democracy. The remaining chapters are devoted to the question of efficiency, which has been central to economic debates about ownership and control. The orthodox belief amongst economists is that any shift to more democratic forms of ent.